(untitled) (Journal Of Educational and Psychological Researches, 2018)
The study seeks the relationship between the mathematical-procedural Knowledge and the logical-mathematical intelligence among students at the third stage in mathematics department. To this end, three questions were arisen: what is the level of mathematical-procedural Knowledge among the third stage students in mathematics department regarding their gender? Do male or female students have more logical-mathematical intelligence and are there significant differences base on their gender? What kind of correlation is between the level of mathematical-procedural Knowledge and the logical-mathematical intelligence of male and female students in the third stage in the mathematics department? A sample of (75) male and female students at the third stage in mathematics department were selected from college of education for pure sciences University of Baghdad. The researcher has developed two scales: one to measure the mathematical-procedural Knowledge consisted of (8) items, and the other to measure logical-mathematical intelligence composed of (10) items. The findings revealed a correlation relationship between the mathematical-procedural Knowledge and the logical-mathematical intelligence foe sample as a whole. It also found students have logical-mathematical intelligence comparing to the mathematical-procedural Knowledge that showed a low level.